Odpowiedzi

Najlepsza Odpowiedź!
2010-03-17T19:47:23+01:00
D)
-(2x-1)=4
-2x+1=4
1-4=2x
2x=-3 /:2
x=-1,5

e)
2(x+1)=x
2x+2=x
2x-x=-2
x=-2

f)
2t-(3t+1t)=6
2t-4t=6
-6=2t /:2
t=-3

g)
-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10

h)
3(y+6)-y=2(y+9)
3y+18-y=2y+18
0=0

i)
(x-7)-2(3x+5)=3
x-7-6x-10=3
-17-3=5x
5x=-20 /:5
x=-4
1 5 1
2010-03-17T19:50:11+01:00
-(2x-1)=4
-2x+1=4 /-1
-2x=4-1/:-2
x=-1,5

2(x+1)=x
2x+2=x/-2x
2= -x/*-1
x=-2

2t-(3t+1t)=6
2t-4t=6
-2t=6/:-2
t=-3

-(4+x)=2(3-x)
-4-x=6-2x/+2x+4
-x+2x=6+4
x=10


3(y+6)-y=2(y+9)
3y+18-y=2y+18
0=0

(x-7)-2(3x+5)=3
x-7-6x-10=3
-17-3=5x
5x=-20 /:5
x=-4
1 1 1
2010-03-17T19:53:07+01:00

d) -(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3 I :(-2)
x=-1,5

e) 2(x+1)=x
2x+2=x I-2x
x=-2
f) 2t-(3t+1t)=6
2t-3t-t=6
-2t=6 I :(-2)
t=-3
g)-(4+x)=2(3-x)
-4-x=6-2x I +2x
x-4=6
x=10

h)3(y+6)-y=2(y+9)
3y+18-y=2y+18
2y+18=2y+18 I -2y
0=0

i)(x-7)-2(3x+5)=3
x-7-6x-10=3
-5x-17=3 I +17
-5x=20 I :(-5)
x=-4